The Artistic Embodiment of the Historiosophical Concept in the D.S. Merezhkovsky’s Novels - Nellya M. Shchedrina (Studia Litterarum)
The review gives a general description of T.I. Dronova’s monograph “D.S. Merezhkovsky’s Historiosophical Novel in the Perspective of the 20th Century,” published in 2021 by the Saratov University Publishing House. The analysis of the book structure reveals the original concept of the historiosophical novel, which is presented by the author. The postulates of the research are based on theoretical studies and results of the genesis and genre novelty’s study of the historiosophical novel of the writer-thinker, as well as on the serious methodological basis and fundamental historical and literary works. The author of the monograph appeals to the controversial issues of the genre in modern literary studies and identifies the dominant and meaningful content of the concept “historiosophical novel.” The problem gets a practical solution in the analytical chapters. The transfer of the attention from the religious and philosophical concept of the writer-thinker to the cognitional method of history and the analysis of poetics prioritizes in further. It is declared that the attitude to history as a text leads D.S. Merezhkovsky to the aestheticization of the Past. The paradoxical nature of genre synthesis in the historiosophical novel, which T.I. Dronova brought out due to the conjugation of concrete historical and metahistorical narrative plans, has a deep impression. The monograph convincingly reveals the features of the artistic embodiment of the author’s historiosophical concept in the trilogy Christ and the Antichrist, as D.S. Merezhkovsky leads the reader outside the concrete historical epoch to metahistorical conflicts. The question of the nature of artistic historicism in the trilogy The Kingdom of the Beast is actualized, the author analyses the importance of the “historicity of narrative” problem for the Writer. A large section of the monograph about the nature of connections in the prose of the 1920–1930s (A. Platonov, M. Bulgakov, M. Aldanov) with D. Merezhkovsky’s works is also of interest.